Taxonomic revision of the parrot snake Leptophis ahaetulla(Serpentes, Colubridae) - de Albuquerque, Nelson Rufino; Fernandes, Daniel S. (Zootaxa, 2022)
The Neotropical parrot snake genus Leptophis comprises a group of 12 colubrine snakes widely distributed in Mexico, Central- and South America. Among the currently recognized taxa in the genus, L. ahaetulla constitutes a morphologically diverse assemblage of typically slender snakes, with subspecies recorded from Mexico to most of South America. Though extremely variable in scalation, coloration, size and dentition, many of these subspecies are still poorly known, with at least three being known from few specimens, hampering the diagnosability and determination of the taxonomic status of certain populations. Accumulation of new specimens and new analytical approach for species delimitation supported a comprehensive taxonomic revision of these snakes based on the examination of meristic, morphometric, color pattern and hemipenial characters of 1625 specimens. Accordingly, the following taxa are herein referred to as full species: L. a. ahaetulla, L. a. bocourti, L. a. bolivianus, L. a. liocercus, L. a. marginatus, L. a. nigromarginatus, L. a. occidentalis, L. a. praestans and L. a. urostictus. Moreover, L. a. ortoni is placed in the synonymy of L. nigromarginatus, whereas L. coeruleodorsus, a former subspecies recently elevated to species rank, is redescribed, and L. haileyi is placed in the synonymy of this latter taxon. In addition, a dichotomous key including all recognized species of Leptophis is provided.